The relationship between responsible leadership and individual work behaviors: The mediating role of affective commitment - Simões, L. (2022)
Aims: Recent scandals within the organizational world have bring to light ethical lapses which have discredit organizations, namely in the way they operate in the market, in the type of leaders they have, leading to a strain in the relationship and trust of their stakeholders (Voegtlin et al., 2012; Waldman & Siegel, 2008). With this in mind, a new type of leadership has been called to respond to the challenges organizations are facing - responsible leadership. This leadership type has been related to different consequents (Miska & Mendenhall, 2018), including employees’ attitudes and behaviors at work (Haque et al., 2017; Voegtlin, 2011). Focusing in this relevant stakeholder group, this study aims to further analyze the relationship between responsible leadership and individual behaviors at work (individual performance and organizational citizenship behaviors) and whether employees’ affective commitment to the organization mediates the former relationship. Methodology / Approach: In order to empirically analyze the research model, a quantitative correlational approach was used. The data were collected through an online survey. 298 Portuguese employees from different organizations have answered, voluntarily and anonymously, to the survey. This included previously validated measures selected from the relevant literature (e.g. Voegtlin, 2011) and socio-professional questions. Conclusions / Results: The data were analyzed using PROCESS macro for IBM SPSS 26. The results indicated that there is significant direct relationship between employees’ perceptions of responsible leadership and their individual behaviors. In addition, affective commitment significantly mediates the relationship between responsible leadership and individual work behaviors, both individual performance and organizational citizenship behaviors. Therefore, the findings, suggest that responsible leaders promote employee’s affective bond to the organization, which reinforces individual performance and organizational citizenship behaviors. Research implications: By having responsible leadership, organizations will be able to increase their employee’s affective commitment, and consequently, increase their individual performance and organizational citizenship behaviors. These behaviors are important to improve overall company’s performance and organizational success. Originality: In this investigation, an employee-centered approach to their perspective on responsible leadership and how it influences their affective commitment and their individual work behaviors was used. With this approach, the study has answered to calls for further analysis of responsible leadership’s consequents at the individual level of analysis (Haque et al., 2017; Miska & Mendenhall, 2018).